The Influence of Service Quality, Promotion and Location on Customer Satisfaction at Artotel Thamrin, Jakarta - Syavira Salsabila; Heidi Reza Rulianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The author of the research aims to determine the effect of service quality, promotion, and location on customer satisfaction at ARTOTEL Thamrin Jakarta. This study collected data from guests staying at ARTOTEL Thamrin Jakarta between March and April 2023. The data collection technique used a questionnaire, which was previously tested for validity and reliability. The collected data were analyzed using multiple regression analysis in SPSS 26 for Windows. The research findings show that service quality, promotion, and location together have a significant influence on customer satisfaction. In particular, promotion and location variables were found to have a significant positive effect on customer satisfaction, while service quality was not observed to have a significant effect on customer satisfaction.